Business ethics and managerial values : concepts, issues and dilemmas in shaping ethical culture for competitive advantage of organisations (Deep & Deep Publications, 2003)
An valuable reference source and practical tool for business leaders for enhancing integrity, reputation and comparative advantage of their organization. A reference guide for the book shelf of managers and management students